Hyaluronic acid-ibuprofen conjugation: a novel ototherapeutic approach protecting inner ear cells from inflammation-mediated damage - Birru, Bhaskar; Veit, Joachim G. S.; Arrigali, Elizabeth M.; Van Tine, Jack; Barrett-Catton, Emma; Tonnerre, Zachary; Diaz, Philippe; Serban, Monica A. (Frontiers in Pharmacology, 2024)
There is a substantial need of effective drugs for the treatment of hearing loss, which affects nearly 500 million individuals globally. Hearing loss can be the result of intense or prolonged noise exposure, ototoxic drugs, infections, and trauma, which trigger inflammatory signaling cascades that lead to irreversible damage to cochlear structures. To address this, we developed and characterized a series of covalent conjugates of anti-inflammatory drugs to hyaluronic acid (HA), for potential use as topical ototherapeutics. These conjugates were tested in in vitro assays designed to mirror physiological processes typically observed with acoustic trauma. Intense noise exposure leads to macrophage recruitment to the cochlea and subsequent inflammatory damage to sensory cells. We therefore first tested our conjugates’ ability to reduce the release of inflammatory cytokines in macrophages. This anti-inflammatory effect on macrophages also translated to increased cochlear cell viability. In our initial screening, one conjugate, ibuprofen-HA, demonstrated significantly higher anti-inflammatory potential than its counterparts. Subsequent cytokine release profiling of ibuprofen-HA further confirmed its ability to reduce a wider range of inflammatory markers, to a greater extent than its equivalent unconjugated drug. The conjugate’s potential as a topical therapeutic was then assessed in previously developed tympanic and round window membrane tissue permeation models. As expected, our data indicate that the conjugate has limited tympanic membrane model permeability; however, it readily permeated the round window membrane model and to a greater extent than the unconjugated drug. Interestingly, our data also revealed that ibuprofen-HA was well tolerated in cellular and tissue cytocompatibility assays, whereas the unconjugated drug displayed significant cytotoxicity at equivalent concentrations. Moreover, our data highlighted the importance of chemical conjugation of ibuprofen to HA; the conjugate had improved anti-inflammatory effects, significantly reduced cytotoxicity, and is more suitable for therapeutic formulation. Overall, this work suggests that ibuprofen-HA could be a promising safe and effective topical ototherapeutic for inflammation-mediated cochlear damage.